2018
DOI: 10.1021/acs.energyfuels.7b02564
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Exhaust Gas Recirculation-Loop Reforming for High Efficiency in a Stoichiometric Spark-Ignited Engine through Thermochemical Recuperation and Dilution Limit Extension, Part 1: Catalyst Performance

Abstract: The use of fuel reformate from catalytic processes is known to have beneficial effects on the spark-ignited combustion process through enhanced dilution tolerance and decreased combustion duration, but, in many cases, reformate generation can incur a significant fuel penalty. In this two-part investigation, we demonstrate that efficient catalytic fuel reforming can result in improved brake engine efficiency while maintaining stoichiometric exhaust under the right conditions. In Part 1 of this investigation, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…H 2 concentration as a function of oxygen catalyst flow and Φ catalyst at the catalyst inlet for (a) catalyst-out concentration from the catalyst mapping study and (b) intake manifold concentration for the multicylinder experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…H 2 concentration as a function of oxygen catalyst flow and Φ catalyst at the catalyst inlet for (a) catalyst-out concentration from the catalyst mapping study and (b) intake manifold concentration for the multicylinder experiments.…”
Section: Resultsmentioning
confidence: 99%
“…In the companion paper (Part 1, "Catalyst Performance"), we reported on the reformer catalyst performance over a range of Φ catalyst conditions in an effort to find a balance between the POx activity required for catalyst durability and the endothermic steam reforming reactions required to minimize energy losses or to achieve TCR during reforming. 48 In this paper, we characterize the multicylinder engine performance while maintaining stoichiometric exhaust emissions with the EGR-loop reforming strategy, focusing on whole-engine performance, including dilution tolerance, combustion performance, and brake thermal efficiency.…”
Section: Wgsmentioning
confidence: 99%
“…Overall, it was found that partial oxidation reforming of liquid fuels in a simulated EGR mixture over the Rh/Al 2 O 3 catalyst demonstrated sufficiently high reformate yields and favorable energetics to warrant further evaluation in the EGR system of a stoichiometric combustion engine. 49,50 The net impact of EGR loop reforming on engine efficiency will be dependent on EGR gas temperature and composition as well as fuel properties. Future studies will investigate the durability of this process.…”
Section: Energy and Fuelsmentioning
confidence: 99%
“…The direct contact is preferred because it provides a better heat transfer and the combustion products can be used as an additional reactant. The hot gas is the EGR mixture (reformed-EGR concept) [30], or is the exhaust of one cylinder [31,32]. In the first one, the fuel is injected into the EGR loop, upstream the catalyst and reacted with water vapor and/or CO 2 in the exhaust over the catalyst to produce syngas (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The additional fuel injects at the end of the expansion stroke, to provide a fuel rich mixture (with oxygen left from the combustion) and feed it into the catalyst during the exhaust stroke. [31] which is located inside the exhaust system of that cylinder. The products then recirculate back to the intake to mix with the air of the other cylinders.…”
Section: Introductionmentioning
confidence: 99%